A utilização do jogo “Meu Momento: sistema reprodutor humano e sexualidade” e a aprendizagem significativa no ensino de ciências - Primak, Ana Carla Mila (2020)
This study has as a starting point to understand questions arising from the adolescents themselves on the theme body & sexuality, considering mainly a technological scenario where everyone can develop their own theories and certainties. In this context, the objective of this investigative work was to verify the contributions of the game “Meu Momento: human reproductive system and sexuality” to the significant learning of sexuality in elementary school. The methodological approach is qualitative, of an interpretative nature with participant observation, with a view to unveiling the interfaces the investigated process that had as a locus a state school in the city of Guarapuava-Pr, in 2019. Data collection included the following steps: one initial survey on information about sexuality only in the 8ºB experimental class, the application of pre and post-test in two classes, the 8th year A, control class (TC) and in the 8ºB, experimental class (TE) and diary notes on board. The educational product presented had as a proposal to offer science / biology teachers a guide for making the game, with a didactic strategy to apply the content on the human reproductive system, as well as to clarify the whole scope of the term sexuality. As a result of reading the data, it is possible to affirm that in class (TE) 8ºB, where the game was applied, it surpassed the performance compared with the class (TC) 8º A. It was also verified that the didactic game when dealing with the theme about the human reproductive system and sexuality can assist teachers who work in the area of science education and as a consequence promote the clarification of students' questions.